Rayleigh Model for Electromagnetic Scattering from a Chiral Sphere. (2015) - Shang, Qing Chao; Wu, Zhen Sen; Qu, Tan; Li, Zheng Jun
Abstract: Rayleigh model has been proposed to deal with scattering from a small sized chiral sphere. A chiral sphere in Rayleigh size illuminated by electromagnetic waves can be substituted by four Hertzian dipoles. Thus the scattering problem is converted to a radiation problem. The four equivalent dipole moments are solved by applying the boundary conditions of Maxwell equations. Numerical results calculated by the model are compared with analytical solutions and achieve good agreement. Scattering patterns of a small chiral sphere with different chirality parameters are depicted and the effects of the chirality are discussed.